Use of digital technologies among First Nations children: Findings from the Longitudinal Study of Indigenous Children - (:unkn) unknown (Commonwealth of Australia, 2024)
The research paper examines how First Nations children's use of digital technologies has changed over time, and how it differs by socioeconomic background.
Keywords: Adolescents and youth; Childhood and child development